The effect of sheet thickness to formability using hyperform - Fatin Zulaikha, Mohd Hatanan (2016)
In this modern era the demand for reducing the vehicle weight for improved the fuel efficiency and structure stiffness for safety is high. Therefore, it will lead to the use of the advanced high strength steel (AHSS). It has been a trend in automotive and aircraft industry. Thus, sheet metal from various thicknesses are selected to be use in many auto parts. The purpose of this project is to determine the influence of sheet from various thicknesses to their formability by determining the forming limit diagram (FLD) of the sheet metal. The method that are used to perform the analysis is the finite element simulation in the Hyperform module of Altair’s Hyperwork. The incremental radioss analysis is used with single action draw and shell element is selected. Several parameters such as blank holder force and punch velocity have been controlled. The punch size and press force is constant for all the conducted simulation. After the simulations, the FLD and percentage of thinning are studied in Hyperview module. After result and data are produced several conclusion can be made in order to improve the quality and for better performance of the project.